2019
DOI: 10.3390/infrastructures4020032
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Ensemble Empirical Mode Decomposition for the Identification of Bridge Frequency from the Responses Measured in a Passing Vehicle

Abstract: In this paper, ensemble empirical mode decomposition (EEMD) and empirical mode decomposition (EMD) methods are used for the effective identification of bridge natural frequencies from drive-by measurements. A vehicle bridge interaction (VBI) model is created using the finite element (FE) method in Matlab. The EMD is employed to decompose the signals measured on the vehicle to their main components. It is shown that the bridge component of the response measured on the vehicle can be extracted using the EMD meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The ability of this method to overcome the mode mixing problem in the SHM field has been surpassed by other modern decomposition methods. 33 The evolution of methods that emerged from EMD describe a successive improvement. For example, the EEMD method defines the IMF component as a mean of ensemble of trails, having white noise as well as signal.…”
Section: Empirical Mode Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of this method to overcome the mode mixing problem in the SHM field has been surpassed by other modern decomposition methods. 33 The evolution of methods that emerged from EMD describe a successive improvement. For example, the EEMD method defines the IMF component as a mean of ensemble of trails, having white noise as well as signal.…”
Section: Empirical Mode Decompositionmentioning
confidence: 99%
“…EMD uses all the extrema to construct the envelopes and the problem arises when the signal contains intermittent processes, since the phenomenon of mode mixing can occur. The ability of this method to overcome the mode mixing problem in the SHM field has been surpassed by other modern decomposition methods 33 …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The IMFs extracted from vehicle response were used as damage indicators of bridge structure (Kildashti et al, 2020; O’Brien et al, 2017). EEMD method introduced by Wu and Huang (2009) to address the mode mixing problem of the EMD was used to identify bridge modal frequencies from vehicle response (Zhu and Malekjafarian, 2019). The results showed that EEMD method provided better performance on the decomposition of vehicle responses compared to EMD.…”
Section: Introductionmentioning
confidence: 99%
“…For that problem, Wu and Huang (2009) propose a noise-assisted analysis approach called Ensemble Empirical Mode Decomposition (EEMD) [ 35 ] that can address the mode mixing problem of the EMD [ 35 , 49 ]. Zhu and Malekjafarian [ 50 ] have recently proposed an EEMD based drive-by approach for estimating bridge natural frequencies from vehicle responses. They suggest that EEMD is less sensitive to measurement noise and provides higher accuracy of bridge first natural frequency from the vehicle responses.…”
Section: Introductionmentioning
confidence: 99%